Composite of Polylactic Acid/Chitosan/Ag-Hydroxyapatite Synthesized Using Turmeric Leaves Extract-Mediated Silver Nanoparticle and Snail Shell as Antibacterial Material - Rahmania Audita; Khoirunisa khoirunisa; Hasna' Azizah Azzahra'; Bambang Hernawan Nugroho; Habibi Hidayat; Is Fatimah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The development of an antibacterial composite of polylactic acid/chitosan/silver nanoparticle-doped hydroxyapatite has been synthesized. The composite was prepared using the silver nanoparticles (AgNPs) green synthesized by using turmeric (Curcuma longa Linn) leaves extract-mediated AgNPs and snail shell as biogenic calcium for hydroxyapatite synthesis. The precipitation method of hydroxyapatite by the doping of AgNPs was the first step, followed by composting with polylactic acid and chitosan as the polymer binder. Physicochemical characterization of the material was studied by using XRD, SEM, and FTIR analyses, and the antibacterial catalytic performance was examined against Escherichia coli (E. coli). The results showed that the synthesized AgNPs are within the <100 nm range in size and not significantly influence the crystallinity of the Ag/HAp. The composite materials maintained the antibacterial activity against E. coli.